Intercoronary connection with bidirectional blood flow and concentric left ventricular hypertrophy - Meireles, George César Ximenes; Abreu Filho , Luciano Mauricio (São Paulo Medical Journal, 1994)
Cardiac catheterization in a 55-year-old man, with a 6-month history of atypical chest pain and Q-waves in D1, Dili and AVF, showed concentric left ventricular (LV) hypertrophy and a large intercoronary connection between right coronary artery (RCA) and circumflex artery (CX), with bidirectional blood flow. Although the RCA and CX were normal, selective injection of CX filled RCA retrogradely and in the same way selective injection of RCA filled CX. Possible mechanisms and literature are reviewed.